2014
DOI: 10.4103/0970-9371.130689
|View full text |Cite
|
Sign up to set email alerts
|

Lipomatous pleomorphic adenoma in the hard palate: Report of a rare case with cyto-histo correlation and review

Abstract: Pleomorphic adenoma is the most common benign tumor of the salivary glands. They are usually composed of epithelial/myoepithelial cells and chondromyxoid stroma. Extensive lipomatous differentiation is very rare. We report a case of lipomatous pleomorphic adenoma (LPA) that presented with a mass in the hard palate of a 32-year-old woman. The fine-needle aspiration cytology material was reported as benign cytology consistent with adenoma with major adipocytic component. Histopathological examination of the exci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 8 publications
0
7
0
Order By: Relevance
“…Since the lipomatous pleomorphic adenoma is a fairly rare neoplasm, there were no reports of recurrence or malignant transformation in any of the reported LPA cases [4]. The patient in our report has also been free of any recurrence or malignant transformation to date.…”
Section: Discussionmentioning
confidence: 48%
See 2 more Smart Citations
“…Since the lipomatous pleomorphic adenoma is a fairly rare neoplasm, there were no reports of recurrence or malignant transformation in any of the reported LPA cases [4]. The patient in our report has also been free of any recurrence or malignant transformation to date.…”
Section: Discussionmentioning
confidence: 48%
“…The stromal element demonstrates varying degrees of myxoid, hyaline, cartilaginous, or osseous differentiation [3]. A lipomatous component may also be seen but prominent lipomatous differentiation is a rare variation of pleomorphic adenoma [4].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ng et al (1995) first reported case of PA with extensive lipometaplasia in submandibular glands. 2,3 Seifert et al defined lipomatous PA as pleomorphic adenoma with more than 90% lipomatous component of total tumour. 4 Haskel et al suggested myoepithelial origin for lipometaplasia as they have ability to transform into various metaplasia.…”
Section: Discussionmentioning
confidence: 99%
“…MTS shares some features with pleomorphic adenoma of the salivary gland (1,9). To the best of our knowledge, 16 cases of pleomorphic adenoma with predominant adipocytes in the salivary gland has been reported, and the proportion of the tumor that was occupied by adipose tissue ranged from 25% to more than 95% (19)(20)(21). Thus a prominent adipocytic metaplastic pattern is rare in both MTS and pleomorphic adenoma.…”
Section: Discussionmentioning
confidence: 99%